2017
DOI: 10.1159/000477447
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular DNA Contributes to Dental Biofilm Stability

Abstract: Extracellular DNA (eDNA) is a major matrix component of many bacterial biofilms. While the presence of eDNA and its role in biofilm stability have been demonstrated for several laboratory biofilms of oral bacteria, there is no data available on the presence and function of eDNA in in vivo grown dental biofilms. This study aimed to determine whether eDNA was part of the matrix in biofilms grown in situ in the absence of sucrose and whether treatment with DNase dispersed biofilms grown for 2.5, 5, 7.5, 16.5, or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 39 publications
3
25
0
Order By: Relevance
“…The mature biofilm may still have e-DNA in the matrix but strengthening of the matrix by methods other than e-DNA in mature biofilms might render DNase ineffective. The results obtained in the current study are in complete agreement with a very recently published study wherein the antibiofilm effect of DNase was reported to be diminishing with the advancing age of biofilm [ 34 ]. Moreover, the efficacy of DNase is also dependent on availability of Mg 2+ ion as discussed in detail in the following section.…”
Section: Discussionsupporting
confidence: 92%
“…The mature biofilm may still have e-DNA in the matrix but strengthening of the matrix by methods other than e-DNA in mature biofilms might render DNase ineffective. The results obtained in the current study are in complete agreement with a very recently published study wherein the antibiofilm effect of DNase was reported to be diminishing with the advancing age of biofilm [ 34 ]. Moreover, the efficacy of DNase is also dependent on availability of Mg 2+ ion as discussed in detail in the following section.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, microbial aggregation during aerobic granulation and consequently biomass density and size are positively affected by increased exDNA amounts (Xiong and Liu 2012 ). In oral biofilms, the exDNA consists not only of microbial but also of host-DNA but exhibits similar functions than in other biofilms (reviewed by Jakubovics and Burgess 2015 ; Schlafer et al 2017 ).…”
Section: Biofilmsmentioning
confidence: 99%
“…Biofilm formation within the gut is now receiving more interest as a mechanism of immune dysregulation, tipping the scales between Th17 and Treg cells. Dalpke et al (2006) described the activation of TLR-9 via bacterial cell contents including DNA, a major constituent of bacterial biofilms ( Schlafer et al, 2017 ). Interestingly biofilm formation has been implicated in the development of systemic lupus erythematosus (SLE), where a structural protein of the biofilm called a curli (amyloid fibril) was capable of binding to bacterial DNA, creating an immunogenic complex inducing an immune response via DC presentation ( Gallo et al, 2015 ).…”
Section: The Gut Microbiome and Ramentioning
confidence: 99%